2013
DOI: 10.1001/jamaoto.2013.92
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Neural Anosmia by Topical Application of Basic Fibroblast Growth Factor–Gelatin Hydrogel in the Nasal Cavity

Abstract: As a gelatin hydrogel degrades slowly in the body, bFGF is gradually released around the site of the lesion; thus, it constantly exerts its effects on neural regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…There are four different types of cells in the olfactory neuroepithelium: mature, immature, basal cells, and supporting cells. Basal cells are located in the bottom epithelial layer and are the only neuronal cells capable of regeneration, unlike in other sensory organs . Therefore, treatment is possible by using the regenerative potential of the basal membrane.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There are four different types of cells in the olfactory neuroepithelium: mature, immature, basal cells, and supporting cells. Basal cells are located in the bottom epithelial layer and are the only neuronal cells capable of regeneration, unlike in other sensory organs . Therefore, treatment is possible by using the regenerative potential of the basal membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al reported a significant improvement in anosmia after olfactory neuroepithelial stem cell transplantation in mice . Nota et al found significant improvement in anosmia in their study group (anosmia‐induced mice) after infiltration of basic fibroblast growth factor (bFGF) …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations